Analisis Laporan Keuangan Secara Historis dan Forecasting - Fitrina Lestari; Husnul Salsabila (Universitas Nusa Putra, 2022)
In a company, financial statements have an important role as a basis for assessing the health of the company in a certain period of time. However, some companies still not use financial statements properly and correctly. This happened in one of the private companies, namely PT. TDI which has never been analyzed their financial statements deeply. This is what underlies a research study on the financial statements of PT. TDI to analyze the company's financial statements from the period 2017, 2018, 2019 and 2020. The purpose of this study is to determine the condition of the company's financial statements in a predetermined period of time and the company's financial condition in the future. This research uses ratio analysis method, forecasting method and scenario analysis. The results show that the liquidity and profitability ratios have decreased from 2017-2020 while the solvency ratio has increased from 2017-2020. In research using the forecasting method, the company's financial condition is still quite good if income continues to rise even though the economy is deteriorating (worst case).